Forces Shaping Working Capital Management Practices: A Preliminary Study - Mohd Ridzuan, Darun; Jamal, Roudaki; Radford, Jack (Medwell Journals, 2015)
This exploratory study is an attempt to identify forces that influence working capital management practices. Focus groups and unstructured interviews were conducted to identify factors influencing decision making process in working capital particularly in complex organizational settings. The qualitative data analysis showed that organizational context played an important role in working capital management practices. Finally, this study develops a number of propositions and future research directions are suggested.